Leadership styles and corporate entrepreneurship: Small and medium enterprises in Pakistan / Imran Shafique - Imran, Shafique (2016)
Corporate entrepreneurship is one of the most important elements for the survival of organizations in today’s business environment characterized by globalization, technological advancements, and competition. Literature suggests that in order to survive in a dynamic environment, organizations need to promote corporate entrepreneurship through an approach characterized by leadership. Small and medium enterprises (SMEs) are vital for every economy. For Pakistan, SMEs are considered as backbone of the economy with a contribution of 30% and 20% to Gross Domestic Product and exports respectively, moreover, they constitute 90% of total businesses. The focus of this study is to analyze the role of leadership styles (transformational, transactional, and passive-avoidant) to promote corporate entrepreneurship in the manufacturing sector of SMEs in Pakistan. This study has three main objectives. Firstly, to explore the relationship between leadership styles and corporate entrepreneurship; secondly, to distinguish the role of leadership styles in affecting the dimensions of corporate entrepreneurship: innovation, new business venturing, self-renewal, proactivity, and risk-taking; and finally, to define the role of absorptive capacity between leadership styles and corporate entrepreneurship overall and individually with each dimension of corporate entrepreneurship. This study integrates the dispersed scholastic work on transformational leadership, absorptive capacity, and corporate entrepreneurship into one framework. Using survey questionnaire, this framework is then empirically analyzed through applications of structural equation modeling (SEM) in the context of manufacturing SMEs of Pakistan. The results demonstrate that transformational leadership positively affects the corporate entrepreneurship and its dimensions. Absorptive capacity also mediates the relationship of transformational leadership and corporate entrepreneurship overall and its dimensions. However, transactional leadership has no effect on corporate entrepreneurship overall, directly and through absorptive capacity, but it has a positive effect on proactivity and risk-taking; and dimensions of corporate entrepreneurship. Similarly, passive-avoidant leadership does not affect corporate entrepreneurship overall, directly and indirectly (absorptive capacity), but effects proactivity positively and new business venturing negatively. The in-depth analysis reveals that direct effect of absorptive capacity on corporate entrepreneurship is more than the direct effect of transformational leadership on corporate entrepreneurship overall and with each dimension. Hence, this study shows that not every type of leadership style promote absorptive capacity and corporate entrepreneurship. Instead, transformational leadership is vital to promote both absorptive capacity and corporate entrepreneurship. It is found that transformational leadership promotes corporate entrepreneurship in SMEs of Pakistan more than other leadership styles. In terms of managerial implications, this study suggests to impart and improve transformational leadership skills in the management through appropriate education and training of key personnel of SMEs. In terms of policy implications, this study recommends the formulation of policies in Pakistan (professional education, developing network with local, country and worldwide information sources, training and development, recruiting and selection) to promote corporate entrepreneurship and absorptive capacity in SMEs should play its importance in transformational leadership.